TANGGUNG JAWAB HUKUM DOKTER DI BIDANG PELAYANAN FORENSIK DALAM PEMBUATAN VISUM ET REPERTUM PERKARA PIDANA ASUSILA - Ayu Welly Jovita; Anggraeni Endah Kusumaningrum (Jurnal MHKI, 2022)
Visum et Repertum (VeR) is an official document that can be used as evidence in sexual criminal cases, which is created by a forensic doctor who has legal responsibility. This study presents three research questions, namely the legal responsibility of forensic doctors in the creation of VeR, the obstacles they face, and the legal consequences of any violations in the creation of VeR. The research method used is an empirical juridical approach with qualitative descriptive data analysis using primary and secondary data. The results show that the legal responsibility of forensic doctors in creating VeR is based on Article 179 of the Criminal Procedure Code. The obstacles faced include a lack of personnel who understand forensic medical science, budget constraints to fulfill the necessary facilities and infrastructure, and empathy for victims of sexual crimes. Solutions that can be done include improving the quality of human resources through training, education, and socialization, improving facilities and infrastructure, and socializing with the community to encourage medical actions, such as allowing autopsies on sexual assault victims. The legal consequences of any violations in the creation of VeR can result in criminal punishment and ethical sanctions for doctors.